For kicks - Francis, Dick, 1920- (Michael Joseph, 1965)
This book follows Daniel Roke, an Australian stud farm owner, who takes on an undercover job. He investigates a doping scandal in British horse racing. As he navigates dangers and deception, he uncovers shocking truths about the sport and himself.